Implementasi Undang-Undang No 22 Tahun 2009 - Siregar, Lasdianni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This thesis research is entitled the implementation of Law no. 22 of 2009 Article 77 Paragraph 1 concerning Traffic and Road Transport Rules for Motorcycle Riding in North Padang Lawas Regency. The formulation of the problem in this study is how the implementation of Law no. 22 of 2009 Article 77 paragraph 1 concerning traffic rules and road transportation in riding a motorcycle in the North Padang Lawas Regency. And what are the inhibiting factors for the implementation of Law no. 22 of 2009 article 77 paragraph 1 concerning traffic rules and road transportation in riding a motorcycle. To obtain the results of this study, the researcher used a descriptive qualitative research type.The sources of data in this study were the Head of Traffic and the Padang Bolak Sector Police staff and the community.Secondary data in this research are data taken as supporting and primary data without having to go directly to the field, and data collection methods are observation, interviews and documents.The collected data is analyzed using editing, verification and analysis methods.Based on the results of the study, it is known how the implementation of Law No. 22 of 2009 Article 77 paragraph 1 concerning traffic rules and road transportation in riding a motorcycle in the North Padang Lawas Regency.In the implementation of traffic rules in the North Padang Lawas Regency, it has not been effective in controlling the driving license (SIM) due to law enforcement regulations that are not in accordance with the SOP (Structure of Operational Procedure), and there is no SK (Certificate of Letters) for the appointment of the Raid Implementation, and a Warrant.The inhibiting factors for the implementation of Law no.22 of 2009 article 77 paragraph 1 concerning traffic rules and road transportation in riding motorbikes, namely the lack of socialization of traffic rules, the lack of traffic control personnel, and the exchange of SIP (Session Initiation Protocol) officers who are not continuous.